If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(x + 3) + -1lnc = 5 Reorder the terms: nL(3 + x) + -1lnc = 5 (3 * nL + x * nL) + -1lnc = 5 (3nL + nxL) + -1lnc = 5 Reorder the terms: -1cln + 3nL + nxL = 5 Solving -1cln + 3nL + nxL = 5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3nL' to each side of the equation. -1cln + 3nL + -3nL + nxL = 5 + -3nL Combine like terms: 3nL + -3nL = 0 -1cln + 0 + nxL = 5 + -3nL -1cln + nxL = 5 + -3nL Add '-1nxL' to each side of the equation. -1cln + nxL + -1nxL = 5 + -3nL + -1nxL Combine like terms: nxL + -1nxL = 0 -1cln + 0 = 5 + -3nL + -1nxL -1cln = 5 + -3nL + -1nxL Divide each side by '-1ln'. c = -5l-1n-1 + 3l-1L + l-1xL Simplifying c = -5l-1n-1 + 3l-1L + l-1xL Reorder the terms: c = 3l-1L + -5l-1n-1 + l-1xL
| 5x(x+60)= | | (5x-3)(3x+7)=0 | | 9.2=-log(x) | | 5x^2+5y^2=16 | | 37+26+3s=21 | | h(4x)=3x^2-2 | | 6-1/-3-(-1) | | 4(4)+1=17 | | .50(18x-10)=3x+x+6-2 | | 5x^2+6x-13=41-31x | | 2x^3*y+3x^2*y^2+6x*y^2+6y^3= | | F(50)= | | z/5-4=23/4 | | Z/5-4=11/4 | | X+8whenx=5 | | 5i(8-8i)= | | 6a^3/5a | | c=37.89+0.50x | | 0.16x+10=-1 | | 1/x*0.01171=0.01*(1/x)*0.000117 | | 5(5+a)-2a=2a+5 | | 180=7x-5+5x+19 | | x^4-4x^2+20=0 | | 3x^2-10x+3=3 | | -9x-5=-158 | | -ln(x+5)+ln(x)=ln(6) | | 8/7-3/3 | | 8-3/7-3 | | -4(3x-2)+2=46 | | 90+2x+(x+14)+64=540 | | 122=4+9e | | 3(x+3)+10=2(x+4)+9 |